SWOT Analysis in Performance Accountability of the Yogyakarta City Human Resources Development and Personnel Agency - Mahadiansar Mahadiansar (Center for Maritime Policy Governance Studies (CMPGS), 2024)
The increasing demand for effective governance in public sector institutions necessitates high standards of performance accountability. In this context, the Human Resources Development and Personnel Agency (BKPSDM) of Yogyakarta City plays a crucial role in ensuring the effectiveness and efficiency of civil service management. This study was initiated to examine the performance accountability of BKPSDM Yogyakarta City through a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis, aiming to provide strategic insights for enhancing institutional performance. The primary objective of this research is to identify internal and external factors influencing the performance accountability of the agency and to formulate strategic recommendations based on these findings. The study employed a qualitative-descriptive approach, using documentation methods and SWOT analysis techniques to evaluate the agency’s internal capabilities and external environment. Data were sourced from the agency’s 2024 Government Agency Performance Accountability Report (LAKIP), complemented by policy documents and strategic plans. The findings highlight several strengths, including structured performance planning and consistent implementation of human resource development programs. However, weaknesses were identified, such as suboptimal coordination across units and limited innovation in service delivery. Externally, the agency has opportunities stemming from regulatory support and digital transformation trends, but also faces threats such as budgetary constraints and rapidly changing policy demands. In conclusion, the SWOT analysis provides a comprehensive understanding of the agency’s performance accountability landscape. The results can guide strategic decision-making and the formulation of performance improvement initiatives, contributing to the agency’s long-term effectiveness and public service quality.